Pengaruh Sistem Pengendalian Internal dan Sistem Informasi Akuntansi Terhadap Kualitas Laporan Keuangan di BAPPEDA Provinsi Bengkulu - Arifin Sotomo Gulo; Nina Yulianasari; Iwin Arnova (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2026)
This study aims to determine the effect of Internal Control Systems and Accounting Information Systems on the quality of financial reports at BAPPEDA, Bengkulu Province. This study uses quantitative research using primary data obtained from a questionnaire of BAPPEDA employees in Bengkulu Province. The population in this study were employees of BAPPEDA, Bengkulu Province in 2025. The dependent variables in this study were Internal Control Systems and Accounting Information Systems. The population in this study was 31 respondents. The results of this study indicate that the internal control system has a positive effect on the quality of financial reports with a significance value of 0.000 < 0.05, and the accounting information system has a positive effect on the quality of financial reports with a significance value of 0.004 < 0.05. The results of this study also indicate that the internal control system and accounting information system have a positive and significant effect on the quality of financial reports.